A Highly Sensitive and Stable Dopamine Sensor Using Shuttle-Like α-Fe2O3 Nanoparticles/Electro-Reduced Graphene Oxide Composites. Issue 15 (11th November 2019) - Li, Guangli; Zhong, Peng; Ye, Yabing; Wan, Xuan; Cai, Zhaotian; Yang, Shihui; Xia, Yonghui; Li, Qing; Liu, Jun; He, Quanguo
Abstract : The development of sensitive and stable electrochemical sensors toward dopamine is highly desirable. Herein, a novel voltammetric sensor was developed for the detection of dopamine using shuttle-like α-Fe2 O3 nanoparticles/electro-reduced graphene oxide nanocomposites (S-Fe2 O3 /ErGO). The surface morphology, microstructure, and chemical composition of S-Fe2 O3 /ErGO nanocomposites were investigated by SEM, XRD and Raman spectra, respectively. The electrochemical behavior of Fe2 O3 /ErGO nanocomposite modified glass carbon electrode (S-Fe2 O3 /ErGO/GCE) was studied by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), and the results show that S-Fe2 O3 /ErGO nanocomposites have large electrochemical active area and low charge transfer resistance. The anodic peak current of S-Fe2 O3 /ErGO/GCE increases 1-fold and 37-fold compared to that of ErGO/GCE and S-Fe2 O3 /GCE, respectively, suggesting the remarkably synergistic enhancement effect on the electrooxidation of dopamine. The anodic peak current is proportional to the concentration of dopamine over the range of 0.01 μM–2 μM. However, the logarithm of anodic peak current versus logarithm of dopamine concentration is linearly related in the range of 2 μM–80 μM. The detection limit (3σ/s) and sensitivity are estimated to be 1.15 nM and 95.57 μA μM −1 cm −1, respectively. Moreover, S-Fe2 O3 /ErGO/GCE also showed good anti-interference, reproducibility and stability. Finally, the proposed S-Fe2 O3 /ErGO/GCE was successfully employed to determinate dopamine in the human serum samples with satisfactory results.